2010
DOI: 10.1002/pits.20509
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' judgments of students' early literacy skills measured by the Early Literacy Skills Assessment: Comparisons of teachers with and without assessment administration experience

Abstract: Teacher judgments about students' academic abilities are important for several reasons, including their day‐to‐day instructional decision making. Not surprisingly, previous studies have investigated the accuracy of teachers' judgments about their students' reading abilities. Previous research, however, has not investigated teachers' judgments about students' early literacy skills, nor has previous research systematically examined how teachers' training and use of an objective assessment instrument impact their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
(33 reference statements)
0
13
0
1
Order By: Relevance
“…Hurwitz et al (2007) have already revealed that accuracy grows when teachers are familiar with the tests. Hence, training teachers in administering standardized assessment instruments supports the level of accuracy teachers achieve (Begeny & Buchanan, 2010;Graney, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hurwitz et al (2007) have already revealed that accuracy grows when teachers are familiar with the tests. Hence, training teachers in administering standardized assessment instruments supports the level of accuracy teachers achieve (Begeny & Buchanan, 2010;Graney, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hoge and Coladarci (1989) have argued already that teachers differ in their diagnostic competences. Begeny and Buchanan (2010) suggested that teachers who had received training on the test used in their study, showed higher accuracy in their judgments than their colleagues without training. In line with this, Herppich, Wittwer, Nückles, and Renkl (2013) found out that teacher tutors judged their tutees more accurately than student tutors.…”
Section: Teacher Characteristics Influencing Accuracymentioning
confidence: 93%
“…Previous research has also shown that when teachers lack preparation, or the most recent training in reading terminology, they may misidentify students who are at risk for difficulties or who already have difficulties (Begeny & Buchanan, 2010;Fedora, 2015;Meisinger et al, 2009). This has implications for the methodology of future studies in this area.…”
Section: Variables That May Influence the Accuracy Of Teachers' Judmentioning
confidence: 99%
“…It may also be possible to train teachers to become more objective assessors; scholars have found that training teachers in giving direct assessments of student skills improves their accuracy when estimating their students' performance (Begeny & Buchanan, 2010), and their ability to administer a battery of direct and indirect assessments as intended by measure developers .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite knowledge of the problems associated with teachers' inaccurate perceptions of students' abilities, teacher ratings are being used to assess student achievement nationwide (Kim, Lambert, & Burts, 2013), leaving questions about what factors influence teachers' perceptions of students, particularly in early childhood mathematics, where there is no available research in this area. Once research is available on the factors that influence teachers' perception of students, it may be possible to train teachers to become more objective assessors by engaging them in professional development (Begeny & Buchanan, 2010;.…”
Section: Teacher Perceptions Of Students and Responsiveness To Pd: LImentioning
confidence: 99%